Biofuels from agricultural biomass in Zimbabwe: Feedstock availability and energy potential. (December 2017) - Maqhuzu, Andile B.; Yoshikawa, Kunio; Takahashi, Fumitake
Abstract: Crop residues and animal dung can contribute a significant portion to the biomass available for conversion to biofuels in Zimbabwe. This paper will extend a quantitative methodology involving the use of probability distributions to rigorously address uncertainty in the quantification of this biomass. The results of 100 000 Monte Carlo simulations using Palisade's @Risk tool indicates the following at a 90% confidence interval: 2.55-5.50 million Mg/yr. of crop residue and 2.99-4.99 million Mg/yr. of dung is generated. The total exploitable energy was estimated at an annual mean of 26.6 and 16.9 million GJ for crop residue and dung respectively